2007
DOI: 10.1016/j.cardiores.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CuZn-superoxide dismutase contributes to β-adrenergic receptor-mediated oxidative stress in the heart

Abstract: Sustained beta-AR stimulation transcriptionally downregulates CuZn-SOD in myocardium via the beta1-AR, thereby contributing to beta-AR-mediated oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 33 publications
7
79
0
Order By: Relevance
“…The more severe hypertension and LV remodeling in the CIH-vehicle group at 6 months could be ascribed because of a variety of mechanisms initiated by exposure to CIH. 4,11,12,17,26,27 ROS and L-Ca 2ϩ channel mechanisms might not necessarily be the only standing mechanisms for the exaggerated CV dysfunction at 6 months in the SHR, although they appear to be critical for the initiation and progression of the developmental programming of long-term CV morbidity after CIH in neonatal SHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more severe hypertension and LV remodeling in the CIH-vehicle group at 6 months could be ascribed because of a variety of mechanisms initiated by exposure to CIH. 4,11,12,17,26,27 ROS and L-Ca 2ϩ channel mechanisms might not necessarily be the only standing mechanisms for the exaggerated CV dysfunction at 6 months in the SHR, although they appear to be critical for the initiation and progression of the developmental programming of long-term CV morbidity after CIH in neonatal SHRs.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Imaging was performed under light anesthesia with ketamine (22 mg/kg, IM) and xylazine (2.7 mg/kg, IM), using a Toshiba 380 PowerVision machine and a pediatric broad-band transducer operating at 10-MHz frequency and 120-Hz frame rate. At the age of 6 to 7 months, the following variables were measured: LV end-diastolic and end-systolic diameter (LVEDD and LVESD), anterior wall thickness (AWT) and posterior wall thickness (PWT) at end diastole, and ejection time from the aortic Doppler trace.…”
Section: Echocardiographic Assessment Of LV Functionmentioning
confidence: 99%
“…The following measurements were made during recording or off-line from stored data on video tape after frame-digitization: 1) LV anteroposterior diameter (D, mm), anterior and posterior wall thickness (AWT and PWT, mm, respectively) and SAX cross-sectional area (A, mm 2 ) at end-diastole (ED) and end-systole (ES) [21,22]. LV hypertrophy was additionally assessed by: 1) the relative wall thickness (RWT = EDAWT + EDPWT)/EDD and 2) LV mass (mg): [(EDD+EDAWT+EDPWT) 3 …”
Section: Diabetic Cardiomyopathy In Ove26 Micementioning
confidence: 99%
“…Cardiotoxicity mediated by ISO due to stimulation of b 1 e adrenergic receptor and this stimulation not only rapidly generate ROS, but also depresses the myocardial endogenous antioxidant system leading to cause myocardial IRI. 30,31 Depletion in the level of myocardial endogenous antioxidants develops a divergence of mitochondrial function. It has already reported that the decrease in the antioxidant level resulted in a diminished hunt of free radical in the ISOeinduced myocardial damage in rats.…”
Section: Resultsmentioning
confidence: 99%